Registration of multiple user defined functions (2023)
The subject technology receives a set of files corresponding to a library, the library comprising a set of functions included in the set of files. The subject technology parses the set of files. The subject technology identifies a set of functions in the set of files based on the parsing. The subject technology, for each function, registers the function as a user defined function (UDF) based on a set of input parameters utilized by the function and a type of parameter of each of the input parameters. The subject technology provides access to each registered function in a different application.